2002
DOI: 10.1159/000057702
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stimulus Predictability and Interstimulus Gap on Saccades in Alzheimer’s Disease

Abstract: Objectives: Studies of saccadic eye movement impairment in Alzheimer’s disease (AD) have largely focused on simple reflexive eye movements and the antisaccade task. The effects of manipulating stimulus timing have been little studied. Methods: Fourteen patients with mild to severe AD and 11 age-matched controls were studied on the antisaccade task, while latencies on simultaneous, gap and predictable tasks were recorded from 11 patients and 11 controls. Dementia severity was assessed with the Mini-Mental State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 36 publications
8
33
2
Order By: Relevance
“…Our antisaccade results are similar to those reported for the frontal variant of FTLD (Meyniel et al, 2005). Consistent with other reports of antisaccade impairments in AD (Currie et al, 1991;Abel et al, 2002;Shafiq-Antonacci et al, 2003;Crawford et al, 2005), we found a strong correlation between antisaccade performance and general cognitive status as measured by MMSE score (Table 5). There was no correlation between MMSE score and antisaccade performance in FTLD.…”
Section: Relationship Between Oculomotor Deficit-correlated Regions Osupporting
confidence: 92%
“…Our antisaccade results are similar to those reported for the frontal variant of FTLD (Meyniel et al, 2005). Consistent with other reports of antisaccade impairments in AD (Currie et al, 1991;Abel et al, 2002;Shafiq-Antonacci et al, 2003;Crawford et al, 2005), we found a strong correlation between antisaccade performance and general cognitive status as measured by MMSE score (Table 5). There was no correlation between MMSE score and antisaccade performance in FTLD.…”
Section: Relationship Between Oculomotor Deficit-correlated Regions Osupporting
confidence: 92%
“…7 Furthermore, results from studies looking at the saccadic gain and velocity in AD are controversial; some studies found impairment, 8,14 whereas other studies did not. 9,15 intrusions during attempted fixation; 11 and (2) visual capture by the target in the antisaccadic paradigm, 14,[17][18][19] in which the subject has to suppress a reflexive saccade to a peripheral target and execute an endogenously driven saccade to an equal and opposite location. Interestingly, inhibition errors in the antisaccadic paradigm could be predicted by measures of dementia severity.…”
Section: Clinical Ocular Motor Manifestationsmentioning
confidence: 99%
“…Interestingly, inhibition errors in the antisaccadic paradigm could be predicted by measures of dementia severity. 14,17,18,20 Antisaccades may provide not only a functional index of the dorsolateral prefrontal cortex, which is damaged in the later stages of AD, but also a tool for monitoring the progression of AD. 6 A more recent study 21 used an antisaccadic paradigm as a way of testing inhibitory control in AD patients.…”
Section: Clinical Ocular Motor Manifestationsmentioning
confidence: 99%
“…Predictive saccades have been studied in Alzheimer's disease, but the specific effects due to foreknowledge are not clear (Abel et al, 2002). Alcohol does not appear to impair the use of task-foreknowledge in predictive saccades (Wegner and Fahle, 1999).…”
Section: Foreknowledge In Other Fieldsmentioning
confidence: 99%